2019
DOI: 10.4103/jisp.jisp_165_19
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of the platelet-rich fibrin bandage versus gelatin sponge-assisted palatal wound healing of free gingival graft donor site: A case series

Abstract: Periodontal plastic surgery often involves palatal donor site, thereby creating an open wound that is prone to postoperative complications such as bleeding, pain, and slow healing process. To prevent the same, platelet-rich fibrin (PRF) and gelatin sponge (GS) were utilized equally at the donor site in six patients. Patients were monitored at the 1st, 2nd, 3rd, and 4th weeks after surgery for postoperative discomfort (D), consumption of analgesics during first postoperative week, alteration of sensitivity (AS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 9 publications
0
11
0
1
Order By: Relevance
“…(2022) observed that collagen hemostatic sponge promoted better pain control when associated with hyaluronic acid gel than with periodontal dressing. In comparison to L‐PRF, lower pain levels were obtained for L‐PRF in comparison to collagen hemostatic sponge in three studies (Femminella et al., 2016; Hassan et al., 2020; Sousa et al., 2020), however, collagen hemostatic sponge promoted more less levels of pain in comparison to L‐PRF in one case series (Belkhede et al., 2019). Schinini et al.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…(2022) observed that collagen hemostatic sponge promoted better pain control when associated with hyaluronic acid gel than with periodontal dressing. In comparison to L‐PRF, lower pain levels were obtained for L‐PRF in comparison to collagen hemostatic sponge in three studies (Femminella et al., 2016; Hassan et al., 2020; Sousa et al., 2020), however, collagen hemostatic sponge promoted more less levels of pain in comparison to L‐PRF in one case series (Belkhede et al., 2019). Schinini et al.…”
Section: Resultsmentioning
confidence: 98%
“…Most of included studies evaluating palatal donor sites covered with L‐PRF membranes in comparison to spontaneous healing (Lektemur Alpan & Torumtay Cin, 2020; Reddy et al., 2015; Shakir et al., 2015), non‐eugenol pack (Aravindaksha et al., 2014; Bahammam, 2018; Kulkarni et al., 2014), collagen hemostatic sponge (Femminella et al., 2016; Hassan et al., 2020; Sharma et al., 2019), cyanoacrylate adhesive (Ozcan et al., 2017) and hyaluronic acid gel (Hassan et al., 2020) reported considerably faster healing with L‐PRF membranes. Only one case series (with 3 patients per group) showed superior results for collagen hemostatic sponge in comparison to L‐PRF (Belkhede et al., 2019) and one RCT showed no differences between both groups (Alvarez‐Medina et al., 2023). Two studies reported better healing with palatal donor sites treated with titanium‐prepared platelet‐rich fibrin (T‐PRF) in comparison to collagen hemostatic sponge (Koca‐Ünsal et al., 2022) and acrylic stent (Gülbahar Ustaoglu et al., 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many studies in the literature in which PRF or T‐PRF membrane application as palatal dressing after FGG harvesting; 15,32,35,43,47–49 however, those studies only evaluated the parameters clinically. In this study, the efficiency of T‐PRF application was evaluated radiologically for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…En la práctica clínica, un injerto óseo de tuberosidad maxilar a menudo se ha utilizado como un injerto particulado para el aumento alveolar deficiente o del seno maxilar antes o simultáneamente (11) . La Fibrina Rica en Plaquetas (FRP), es un material biocompatible autógeno y concentrado plaquetario de segunda generación (12) , contiene leucocitos, plaquetas y factores de crecimiento, indispensables para la cicatrización (13).…”
Section: Introducciònunclassified